2021
DOI: 10.3390/jpm11060572
|View full text |Cite
|
Sign up to set email alerts
|

Individual Revision Knee Arthroplasty Is a Safe Limb Salvage Procedure

Abstract: Introduction: Revision total knee arthroplasty after multiple pre-surgeries is challenging. Due to severe bone defects, standard implants for metaphyseal and diaphyseal anchoring may no longer be suitable. The primary aim of this case series is to evaluate the early complication rate for individual knee implants with custom-made cones and stems after two-stage revision with severe bone defects. Methods: Ten patients who were treated with custom-made 3D-printed knee revision implants were included. Inclusion cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
1
0
1
Order By: Relevance
“…They showed a low rate of complications (n = 1) and only reported functional outcomes in three patients (OKS: 41;43;38) [14]. Using a similar treatment approach, Savov et al reported results in 10 patients with 9 custom-made tibial cones, showing a low complication rate (n = 2) at a mean follow-up of 21 months, though no functional outcome parameters were reported [19]. Li et al published a study using a similar method in seven patients with good functional outcomes at a follow-up of 25 months (postoperative HSS: 78 (70-83) (p < 0.01)) [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They showed a low rate of complications (n = 1) and only reported functional outcomes in three patients (OKS: 41;43;38) [14]. Using a similar treatment approach, Savov et al reported results in 10 patients with 9 custom-made tibial cones, showing a low complication rate (n = 2) at a mean follow-up of 21 months, though no functional outcome parameters were reported [19]. Li et al published a study using a similar method in seven patients with good functional outcomes at a follow-up of 25 months (postoperative HSS: 78 (70-83) (p < 0.01)) [20].…”
Section: Discussionmentioning
confidence: 99%
“…While the literature suggests that cones and sleeves might be used interchangeably in smaller defects, we have specifically opted for the use of custom-made sleeves and not cones in our collective due to several factors. The implantation of a CMS should only be indicated when sufficient epiphyseal fixation is no longer possible and metaphyseal fixations are highly compromised [8,19]. In these cases, long-term implant survival can only be achieved by osteointegrative fixation in zones II and III [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В настоящее время все чаще в хирургической практике используются индивидуально изготовленные имплантаты для лечения пациентов с наличием обширных костных дефектов [15]. Однако выбор метода, как правило, определяется предпочтениями хирурга и непосредственной доступностью каждой из технологий в определенном лечебном учреждении [16].…”
Section: Discussionunclassified
“…This has been the case for decades, but the techniques that are available to us are becoming more and more sophisticated and allow better restorations [ 3 , 4 , 5 , 6 ]. The same is actually true for defects in revision arthroplasty and spinal surgery [ 7 , 8 , 9 ]. Since more and more revisions are re-revisions, the defects and collateral damage become bigger with every episode of loosening and consecutive operation.…”
mentioning
confidence: 98%